ASSESSMENT AND INFRASTRUCTURE OF DISTRICT PUBLIC LIBRARY SYSTEM IN KOTA REGION (RAJASTHAN) - Singh, Dr. Gurnam; Shrivastava, Dr.Deepak Kumar (International Journal of Research -GRANTHAALAYAH, 2020)
The public libraries play very important role in fostering the intellectual development of society at large. They support both formal and non-formal education systems of our society. They are considered as People’s University and serve as a center for self-education and lifelong learning. They are considered to be an intellectual power house which strives to fulfill and meet the educational needs of the public through varied resources and services Presented Research Paper reveals that Rajasthan State are need urgent attention on the District Public libraries for lack of staff and insufficient budget. It’s great achievement that in 2006, Library legislation passed in Rajasthan but not seems their major effects till today. I think Rajasthan needs advocacy to run the Public libraries. In Rajasthan, maximum libraries are facing the problem of book losses and no regular basis stock verification done. Hope after reviewing this study Govt. of Rajasthan will observe the pros and cons.